An Efficient Synthesis of 2’-Hydroxychalcones - Makrandi, J.K.; Kumar, Surender (Asian Journal of Chemistry, 2016)
2'-Hydroxychalcones have been synthesized by condensation of 2'-hydroxyacetophenones with aromatic aldehydes in the presence of dehydrated barium hydroxide in dry dimethyl sulphoxide medium.